IMPLEMENTASI KURIKULUM 2013 PADA SEKOLAH DASAR DI KECAMATAN PANGKALAN KOTO BARU KABUPATEN LIMA PULUH KOTA PROVINSI SUMATERA BARAT - Eftwory, Cesno; Rusli. SD, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Implementation of Curriculum 2013 at the elementary school in Pangkalan Koto Baru experiencing various problems because according to socialize standardization is done twice or more. However for the socialization of teachers in the district of Koto new Base is only done once. So the faculty as a human resources do not understand how to implement the curriculum in 2013 in accordance with existing standards. Then the implementing organizations involved establish standard operating procedures for the implementation of the curriculum in 2013. Handbook as infrastructure is inadequate because of delays in the distribution of books of the government for four months. The purpose of this research was to identify and analyze how the implementation of the curriculum in 2013 at the elementary school in Pangkalan Koto Baru and the factors that influence the implementation of the curriculum in 2013.This research using Van Meter Van Horn theory which states that the successful implementation of a policy is the standard and policy objectives , resources, characteristics of the implementing organization , the communication between organizations , the attitude of the implementing policies and social environment , economic and political . This study used a qualitative exploratory methods , techniques of collecting data through observation and interviews where people that involved in this study as an informant.The results showed that the implementation of the curriculum in 2013 at the elementary school in Pangkalan Koto Baru has not been done optimally because there are still many weaknesses in the current curriculum in 2013 is implemented in Pangkalan Koto Baru. Inhibiting factors affecting the implementation of the curriculum in 2013 at the elementary school in Pangkalan Koto Baru is socialization which is not maximized , inadequate means and Standard Operating Procedure ( SOP ) which has not been established .Keywords : Implementation , Curriculum 2013, Elementary School